Epidemiologic Characteristics of Patients with Inflammatory Bowel Disease in Kermanshah, Iran - Zobeiri, Mehdi (Middle East J Dig Dis, 2017)
BACKGROUND This study was done to define some epidemiological aspects of inflammatory bowel disease (IBD), and to describe its characteristics in west of Iran. METHODS In this descriptive study all patient with the diagnosis of IBD who were visited in universityaffiliated medical centers, between 2014 and 2015 were recruited. Their demographic characteristics, disease-related manifestations, complications, disease course and their chief complaints were analyzed. RESULTS Of 156 referred individuals, 153 patients had ulcerative colitis (UC) and 3 patients had Crohn’s diseases (CD). The mean age of the patients at diagnosis was 35.69±12.35 (range: 17-80) years with the most common age group of 25-35 years and slight female predominance (51.9%). More urban patients were registered (90.4%) and 57% had high school or upper education. Positive family history of the disease was in 25.6% and 66.6% had four or more family members. Furthermore, 51.9% had left sided colitis and 40.4% had pancolitis with bloody diarrhea (79.5%) and abdominal pain (68.6%) as the most common manifestations. 36.5% had other autoimmune diseases. Multiple flare was seen in 47.4%, most commonly due to drug discontinuation (26.28%). Hospital admission was reported in 34.6%. History of contraceptive pill use was in 38.8% of the female patients. CONCLUSION The demographic and clinical manifestations of IBD are usually the same as other developing countries; however, the rarity of CD is eminent. Although the accurate epidemiological characteristic of IBD in Iran is still obscure, it is not a rare disease as previously thought and it seems that gradual reception of a western lifestyle may be linked to the ongoing rise in IBD.